How the Jewish communities prepared for peace during the First World War - Gottschalk, Max (New York : Research Institute on Peace and Post-War Problems of the American Jewish Committee, 1943)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: joods vraagstuk; Wereldoorlog 1; Wereldoorlog 2